THE MODELING OF PROCESS NEUTRALIZATION OF PHOSPHORUS OXIDE IN THE ATMOSPHERE - Beliaiev, M. M.; Verhun, O. O.; Kovtun, Yu. V. (Science and Transport Progress, 2009)
A numerical model was used to calculate the process of toxic gas neutralization. The 2D transport model is used to simulate the process. The implicit difference scheme was used. The rsults of numerical experiment are presented.